Producción de bellota en la dehesa: factores influyentes - Rodríguez-Estévez, V.; García, A.; Perea, J.; Mata, C.; Gómez, A. G. (Arch. Zootec, 2007)
This paper reviews the state-of-the- knowledge of acorn production in the South- Western Iberian dehesas. In the first part are briefly described the soil and climatic determining factors and phenology of most common trees of genus Quercus at the dehesa (Q. ilex, Q. suber and Q. faginea). In the second part, acorn production estimations are analyzed. Was established a mean acorn yield of 300 to 700 kg/ ha; with individual productions of 8-14 kg/tree for Q. ilex, 5-10 kg/tree for Q. suber and 1-11 kg/ tree for Q. faginea; with a highly variable production, both between and within years and individual trees. Finally we review the factors affecting acorn production, describing density of trees (estimated in 20-50 trees/ha), masting phenomenon (with cycles of 2-5,5 years and asynchrony between trees), individual cha- racteristics of trees (genetic potential, age, top surface, etc.), tree mass handling (with favourable effect of tilling, moderate pruning and sustainable grazing), meteorological conditions (mainly drought and meteorology during flowering) and sanitary status (Lymantria, Tortrix, Curculio, Cydia, Balaninus and Brenneria).
Keywords: Agro forestry system; evergreen oak; iberian pig; Mast-seeding; Montanera; Quercus

Ecological food production from animal origin in the dehesa agrosystem of Andalucia and Extremadura - Mata, C.; Caballero, I.; Labrador, J.; Casco, J. M. G. (BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS, 1998)
Andalucia and Extremadura gather certain advantages and conditions for the development of ecological stockbreeding which place them among the European territories of greatest potential in this sense. There are wide areas of high environmental balance, some of them declared as Natural Protected Areas-, with soils of only forestal and silvopastoral use, and with a lot of farms used for the traditional extensive stockbreeding. In this area the management is close to the ecological stockbreeding, and the location coincides with the one of dehesa farms. Most of these farms suffer problems derived from the pressure to which they are subjected because of a management towards greater intensification. Their functions are not valued properly. Many times their products are not competitive with the usual market prices. Being, however of greater organoleptic, sanitary, environmental quality and being even greater, their possibility of profitability. The conversion of extensive stockbreeding farms into a type of ecological production may provide solutions to these problems, favouring a consolidated development; and at the same time, it may encourage an action integrated with other agrarian farms, producing sites of pluriactivity and much more profitability. This work shows a description of the most relevant aspects of extensive stockbreeding productions in relation to its conversion into the ecological production.
The following values have no corresponding Zotero field: periodical: BASIS OF THE QUALITY OF TYPICAL MEDITERRANEAN ANIMAL PRODUCTS issue: 90 pub-location: POSTBUS 220, 6700 AE WAGENINGEN, NETHERLANDS
Keywords: animal ecological production; Dehesa

Root respiration, growth and nitrogen uptake of Quercus suber seedlings - Mata, C.; Scheurwater, I.; MartinsLoucao, M. A.; Lambers, H. (PLANT PHYSIOLOGY AND BIOCHEMISTRY, 1996)
We tested the influence of two N-sources, NO3- and NH4+, on root growthand respiration of Quercus suber L. Seedlings were grown on hydroponics with 0.5 mM N as NO3- or NH4+ in a growth chamber. Root relative growth rate (RGR) of NO3--fed seedlings ranged from 9 to 34 mg g(-1) day(-1). These values are lower than those described for slow-growing herbaceous and for most woody species. Root respiration and the activity and capacity of the alternative pathway (AP) showed no differences between the two N-sources. Both activity and capacity of the AP were very low and the cytochrome pathway was fully engaged. Specific respiratory costs were calculated for maintenance, 6.3 nmol O-2 g(-1) s(-1), for nitrate uptake, 0.99 mol O-2 mol N-1, and for growth 5.4 mmol O-2 g(-1). These values are similar to those found for slow-growing herbaceous species. The major part of total root respiration, over 64%, was used for maintenance processes, and a much smaller fraction for growth and nitrate uptake.
The following values have no corresponding Zotero field: pub-location: S P E S-JOURNAL DEPT, 120 BD ST GERMAIN, F-75006 PARIS, FRANCE publisher: GAUTHIER-VILLARS
Keywords: NO3-; NH4+; relative growth rate; root respiration